CHARACTER EDUCATION AND TEACHER CREATIVITY AS PREDICTORS OF STUDENT LEARNING OUTCOMES - Annisa Magfirah Malele; Silvana Shirly Alice Oroh; Febriyanti Maurren Lidya Rattu (CV. TOTUS TUUS, 2026)
Improving achievement in remote schools requires attention to both the ethical conditions that organize student participation and the pedagogical capacity of teachers to adapt instruction. This study examined whether character education and teacher creativity separately and jointly predicted student learning outcomes at a remote Indonesian junior high school. A quantitative cross-sectional explanatory-correlational survey involved 39 students from a population of 43 during the 2025–2026 academic year. Questionnaire, observation, and school-documentation data were analyzed using simple and multiple linear regression. Character education positively predicted learning outcomes (B = 0.743, β = .740, t = 6.684, p < .001) and explained 54.7% of the observed variance. Teacher creativity was also significant (B = 0.740, β = .749, t = 6.884, p < .001) and explained 56.2%. In the joint model, character education (β = .408, p = .010) and teacher creativity (β = .446, p = .005) retained significant unique coefficients, and the model explained 63.6% of outcome variance, F(2, 36) = 31.511, p < .001. The findings indicate that value-oriented school practices and adaptive pedagogy are complementary predictors, although the cross-sectional single-site design does not establish causality. Schools may use the results to align character formation with contextualized instructional improvement. Future multisite, longitudinal, and multilevel studies should employ validated measures and independently verified achievement indicators.